Namādzij Tadrīs Mahārah al-Kalām ‘ala Asās an-Nazhariyyah al-Bināiyyah fi Ma’had Al Muhsinin Kerinci - Abdul Muid (Taqdir, 2020)
This study aimed to analyze the learning model for speaking Arabic in the perspective of constructivism theory at Al Muhsinin Kerinci Islamic Boarding School and teachers’ effort in supporting the learning model used. This study started from the discussion of the concepts and models of Arabic learning that are used in several Islamic Education Institutions such as Islamic boarding schools that require conventional method. Al Muhsinin Islamic Boarding School provides learning concepts that make learning active and interactive which teach Arabic speaking skills. The research method used by researchers in this study was descriptive qualitative analytic research. The results showed that the learning model of Arabic speaking skills at Al Muhsinin Kerinci Islamic Boarding School studied contextual learning models consisting of daily communication activities using Arabic, quantum learning models related to independent learning activities and further learning, cooperative learning models including activities morning vocabulary learning and Arabic conversation and problem based learning models in Arabic discussion. Which learning model has fulfilled the characteristics of constructivism in the form of renewal, elicitation, approval of ideas and comments. Related to teacher assistance in supporting the learning model at Al Muhsinin Kerinci Islamic Boarding School, namely by requiring Arabic in daily life, preparing language courts, and strategies that support the environment such as the management of the Arabic league, which is related to cultural, relationships, motivation, and contextual matters in learning Arabic, specifically learning Arabic speaking skills.